2021
DOI: 10.1037/men0000286
|View full text |Cite
|
Sign up to set email alerts
|

Measurement invariance of three gender ideology scales across cis, trans, and nonbinary gender identities.

Abstract: Popular measures of masculinity and femininity ideologies have been validated primarily with cisgender (cis) samples. The present study assessed the measurement equivalence/invariance (ME/I) of two versions of the Male Role Norms Inventory (MRNI; Short and Very Brief Forms), and the Femininity Ideology Scale-Short Form, across gender broadly conceived to include cis, transgender (trans), and nonbinary gender identities. Participants (N = 1233, 34.3 % trans) were recruited from community and college samples in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In future studies, a more extensive and inclusive approach to the self-assessment of gender should be considered, especially since higher prevalence rates of psychological distress have been reported for transgender and gender-diverse individuals because of minority stressors [67,68], and gender role norm measurements seem to not measure the same constructs in trans-and cis-identified persons [69]. Furthermore, although a strength of the present study is the parallel examination of gender identity with the BSRI and male gender ideology with the MRNS, other aspects of masculinity may be relevant with regard to psychotherapy use prediction in men.…”
Section: Future Directionsmentioning
confidence: 99%
“…In future studies, a more extensive and inclusive approach to the self-assessment of gender should be considered, especially since higher prevalence rates of psychological distress have been reported for transgender and gender-diverse individuals because of minority stressors [67,68], and gender role norm measurements seem to not measure the same constructs in trans-and cis-identified persons [69]. Furthermore, although a strength of the present study is the parallel examination of gender identity with the BSRI and male gender ideology with the MRNS, other aspects of masculinity may be relevant with regard to psychotherapy use prediction in men.…”
Section: Future Directionsmentioning
confidence: 99%
“…More recently, terms such as nonbinary and genderqueer have gained visibility in defining identities which resist the binary conceptions of gender. As with cisgender and transgender populations, differences in gender ideology have also been found between cis, trans, and nonbinary gender identities (McDermott et al, 2021).…”
Section: The Entanglement Of Gender With Other Social Effects On Lang...mentioning
confidence: 99%
“…Fourth, our data did not allow for an examination of the link among cisgender and transgender individuals. Emerging evidence (e.g., McDermott et al, 2021) suggests that nonbinary and transgender individuals might have a distinct understanding of gender ideologies. Should this be the case, our interpretation of findings would be limited to cisgender men and women.…”
Section: Discussionmentioning
confidence: 99%
“…Scholars have indicated that traditional gender ideologies are more likely to be endorsed by straight people than by sexual minority individuals. In particular, North American scholars who focused on TMI noted that these views best reflect the perceptions of White straight men (e.g., McDermott et al, 2021).…”
Section: Gender Ideology and Attitudes Toward Gay Peoplementioning
confidence: 99%